Kajian Sosiolinguistik Alih Kode Terhadap “The Scheunemann, Keluarga Jerman yang Fasih Berbahasa Jawa” dalam Acara Hitam Putih - Ayu Winda Sari; Erni Erni (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
Abstract Humans are individual creatures who cannot be separated from daily social interactions by using language. Individuals involved in language switching usually involve multilingual or multilinguistic matters. Therefore, in communicating, of course, code switching events are very possible. As in this study which raised the title "Switching Code in the episode Hitam Putih episode "The Scheunemann, a German family who is fluent in Javanese". This study uses a qualitative approach and content analysis methods (content analysis). Data collection techniques are listening techniques and note-taking techniques. For data analysis, this study uses the element sorting technique proposed by Sudaryanto (in Muhammad, 2014: 239) and the coding technique proposed by Paul W. Missing (in Bungin, 2008: 165). From the results of the analysis carried out, there are 44 utterances identified as code-switching utterances, including: 1) the types of code-switching found in the Black and White episode of “The Scheunemann”, a German family who is fluent in Javanese; There are 38 inward code switching and 6 outward code switching. 2) the factors that cause code switching are 14, namely: (1) the speaker and the speaker's personality, (2) the change in speech situation, (3) the change of subject matter, (4) evoke a sense of humor, (5) the variety and level of language speech, (6) for mere prestige, (7) there is a sense of familiarity, (8) there is rejection, (9) curiosity, (10) adapts to the interlocutor, (11) there is a challenge from the interlocutor, (12) expresses feelings, (13) affirmation of speech, and (14) to divert the subject. The conclusions of this study are: there are 44 utterances; 38 utterances including inward code switching and 6 utterances including outward code switching, and there are 14 factors that cause code switching.